(untitled) (The Planet, 2024)
Introduction: Calcium is a vital nutrient during pregnancy, essential for fetal development, especially due to its role in maternal-fetal calcium transfer. Previous research has linked low maternal calcium levels to adverse outcomes including low birth weight, complications like preeclampsia and preterm delivery, and reduced fetal bone mineral density. This study aimed to evaluate the impact of calcium supplementation during pregnancy on neonatal birth weight. Methods and materials: This was a cross-sectional study that was conducted in the Department of Obstetrics and Gynecology at the Institute of Child & Mother Health (ICMH), Dhaka, Bangladesh from September 2018 to August 2019. A total of 98 women with uncomplicated, singleton, term pregnancies attending the ICMH were purposefully enrolled as study subjects. Data were processed and analyzed using MS Excel and the SPSS version 22.0 program as necessary. Results: In this study, 80.6% of participants consistently used calcium supplements. Among them, 73.47% had normal serum calcium levels, and 26.53% had low levels. Regular calcium supplement users (98.6%), had statistically significant (p < 0.0001) normal calcium levels. Lower calcium correlated with more low birth weight babies (86.36%). Conversely, 84.21% of normal-weight newborns had mothers with normal calcium levels, also statistically significant (p < 0.0001). Conclusion: This study emphasizes the importance of consistent calcium supplementation during pregnancy for maintaining normal serum calcium levels, which can positively impact birth weight outcomes. It highlights the need to promote and encourage pregnant women to take recommended calcium supplements for maternal and fetal health.